Overview of research on adhesion reduction and desorption technology of soil-contact construction equipment - Li Qiang; Chen Zhikai; Guan Tingting; Wang Jing; Xu XiuJie (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
Earthmoving machinery is prone to adhesion problems when working against soil media, resulting in a decline in construction efficiency and quality. This paper summarizes the development of soil adhesion mechanisms, describes the research progress of experts and scholars in various countries in the field of adhesion and desorption, and prospects the research on adhesion and desorption of soil contacting components of construction machinery.